2014
DOI: 10.1111/and.12371
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal aneuploidies and DNA fragmentation of human spermatozoa from patients exposed to perfluorinated compounds

Abstract: This study investigated chromosomal aneuploidies and DNA damage in spermatozoa from male patients contaminated by perfluorinated compounds (PFCs) in whole blood and seminal plasma. Sperm aneuploidy and diploidy rate for chromosomes 18, X and Y were evaluated by FISH; sperm DNA fragmentation was assessed by terminal deoxynucleotidyl transferase-mediated dUTP nick end-labelling technique coupled to flow cytometry. Our results indicated that PFC contamination was present in 58% of subjects included in the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 34 publications
1
32
0
1
Order By: Relevance
“…A few studies reported on the possible associations between PFAS exposure and sperm DNA integrity and apoptotic markers (Specht et al 2012;Leter et al 2014;Buck Louis et al 2015;Governini et al 2015). PFOA, PFHxS, PFOS and PFNA were not consistently associated with sperm DNA integrity or fragmentation, or apoptotic markers in the study by Specht et al (2012).…”
Section: Semen Characteristicsmentioning
confidence: 82%
See 3 more Smart Citations
“…A few studies reported on the possible associations between PFAS exposure and sperm DNA integrity and apoptotic markers (Specht et al 2012;Leter et al 2014;Buck Louis et al 2015;Governini et al 2015). PFOA, PFHxS, PFOS and PFNA were not consistently associated with sperm DNA integrity or fragmentation, or apoptotic markers in the study by Specht et al (2012).…”
Section: Semen Characteristicsmentioning
confidence: 82%
“…The study by Buck Louis et al (2015) found a lower percentage of sperm with high DNA stainability with higher PFOSA, but no consistent associations for the other PFASs they investigated (Et-PFOSAAcOH, Me-PFOSA-AcOH, PFDA, PFNA, PFOS and PFOA), and none of the PFASs were associated with DNA fragmentation index. Governini et al (2015) found that men with the highest combined PFOA and PFOS levels had a higher DNA fragmentation index and higher rates of sperm aneuploidy, however this study included only 59 men.…”
Section: Semen Characteristicsmentioning
confidence: 87%
See 2 more Smart Citations
“…[40,41] Since both phthalates and PFASs show toxicity and prolonged exposure can affect endocrine function and cause neurodevelopmental disorders and infertility we have calculated the estimated daily ingestion of the contaminants of interest through tuna consumption. [42][43][44][45][46][47][48][49] The tolerable daily intake (TDI) established for DEHP is 0.05 mg/kg, a value that was used in this work as a basis of comparison for the intake of DEHP itself and for the total amount of DEHP and MEHP, being the latter a direct metabolite of DEHP. [12] We calculated the EDI for the general Italian population and for those who claimed to be fish consumers, assuming that their daily fish intake consisted solely of Atlantic bluefin tuna fillets (Table 3).…”
Section: Resultsmentioning
confidence: 99%